Genomic Tools in Pearl Millet Breeding for Drought Tolerance: Status and Prospects - Serba, Desalegn D.; Yadav, R. S. (My University, 2017)
Pearl millet [Penisetum glaucum (L) R. Br.] is a hardy cereal crop grown in the arid and semiarid tropics where other cereals are likely to fail to produce economic yields due to drought and heat stresses. Adaptive evolution, a form of natural selection shaped the crop to grow and yield satisfactorily with limited moisture supply or under periodic water deficits in the soil. Drought tolerance is a complex polygenic trait that various morphological and physiological responses are controlled by 100s of genes and significantly influenced by the environment. The development of genomic tools will have enormous potential to improve the efficiency and precision of conventional breeding. The apparent independent domestication events, highly outcrossing nature and traditional cultivation in stressful environments maintained tremendous amount of polymorphism in pearl millet. This high polymorphism of the crop has been revealed by genome mapping that in turn stimulated the mapping and tagging of genomic regions controlling important traits such as drought tolerance. Mapping of a major QTL for terminal drought tolerance in independent populations envisaged the prospect for the development of molecular breeding in pearl millet. To accelerate genetic gains for drought tolerance targeted novel approaches such as establishment of marker-trait associations, genomic selection tools, genome sequence and genotyping-by-sequencing are still limited. Development and application of high throughput genomic tools need to be intensified to improve the breeding efficiency of pearl millet to minimize the impact of climate change on its production.
Citation: Serba, D. D., & Yadav, R. S. (2016). Genomic Tools in Pearl Millet Breeding for Drought Tolerance: Status and Prospects. Frontiers in Plant Science, 7, 10. doi:10.3389/fpls.2016.01724
Keywords: Pearl Millet; Pennisetum Glaucum; Genomic Tools; Drought Tolerance; Gbs; Qtl